Os desafios da formação de professores indígenas no Magistério Intercultural no Alto-Xingu-MT - Geraldo, Karina Aparecida (2023)
The theme of this research is the training of indigenous teachers and the indigenous school education. The focus is to inquire how the indigenous teacher training linked to the “Indigenous Intercultural Teaching Project of Alto Xingu” occurred. The study focuses specifically on the Leonardo Villas Boas Station in the Alto Xingu area, in the State of Mato Grosso. The Indigenous Intercultural Teaching is an indigenous teaching program that happens inside the respective communities. It is offered by the Secretary of Education of the State of Mato Grosso (SEDUC), in partnership with the National Ministry of Education (MEC), National Indian Foundation (FUNAI), National Health Foundation (FUNASA) and State Council of Indigenous School Education (CEEI). It began in 2005, in the State of Mato Grosso, having the Law 10.172, of January, 2001 as a parameter, in which the National Education Plan intended that the indigenous school education and the indigenous teacher training happen according to their culture and in the space where they are inserted. The aim of the research is to show how the information was organized in this formative process, as well as to suggest some paths that can improve it, as a means of contributing with the State Secretary of Education in their proposals for training teachers and indigenous teachers. It is qualitative research, focusing on a phenomenological method, based on Merleau-Ponty’s philosophy, and Paulo Freire’s educational dimension. The methodology proposes open research with paths that run through the bibliographic, documental research and the researcher’s nonsystematic observations, as a member of SEDUC’s team and a teacher of this training course. Such lived experience, registered through a field diary, can collaborate with important information for this research methodology. Also, as methodological contribution, the text uses a dense description, according to the Geertzian theory. The result of this study shows weaknesses due to lack of more documental information in relation to the formative training process that could not be found. Therefore, the present text aims to describe the social impacts that can be generated and the contributive implications that the research can bring for the ethnic communities involved, in case SEDUC decides to include in its training for the Indigenous Intercultural Teaching Project the contributions of this study in the practice of the methodological-theoretical and pedagogical process accomplished. It is expected that the course can improve the non-indigenous teachers’ pedagogical practices through an Indigenous Intercultural Training Teaching Project in the State of Mato Grosso which seeks social changes that would help, at this time, the well-being of indigenous peoples.